Risk Factors Associated with Perinatal Mortality at Besat Hospital in Sanandaj: A Case-control Study - Leila Hasheminasab; Fariba Ranaei; Jamileh Majidi; Farzaneh Zaheri; Roya Karime (Journal of Midwifery & Reproductive Health, 2021)
Background & aim: Perinatal mortality is used in international scales as a reflection of the quality of maternal and newborn care. Therefore, the current study aimed to determine perinatal mortality and its associated factors at Besat Hospital of Sanandaj, Iran. Methods: This retrospective case-control study was conducted using medical records available at Sanandaj Besat Hospital during 2013- 2015. Sampling was conducted through the census method. Firstly, all cases of perinatal mortalities in the delivery and neonatal wards whose medical files were complete (n=466) were selected as the case group, and a file of live birth for each case was randomly chosen on the same day as the control (n=466). Data analysis was performed by SPSS 21 using the Chi-square, independent samples t-test, and logistic regression. Results: The rate of perinatal mortality was reported as 38.3 per 1,000 births. Parental consanguinity, parity, number of abortions, birth weight, gestational age, pregnancy and delivery complications as well as congenital abnormalities were significantly different between the two groups (p <0.05). The most important risk factors associated with perinatal mortality were prematurity (OR=15.6; 95% CI: 8.7-29.3; p <0.001), low birth weight (OR=0.6; 95% CI: 0.5-0.7; p <0.001), congenital abnormalities (OR=6; 95% CI: 2.2-16.4; p <0.001), pregnancy complications (OR=2.2; 95% CI: 1.1-4.6; p <0.03), delivery complications (OR=2; 95% CI: 1.5-4.7; p <0.001), and parental consanguinity (OR=21.7; 95% CI: 1.23-2.41; p <0.001). Conclusion: Parental consanguinity, LBW, preterm birth, hypertension, and premature rupture of membranes were the most important factors increasing the risk of perinatal mortality.